Impact of Allogeneic Hematopoietic Cell Transplantation (allo-HCT) on the Outcomes of Angioimmunoblastic T-Cell Lymphoma (AITL): A Center for International Blood and Marrow Transplant Research (CIBMTR) Analysis - Epperla, Narendranath; Woo Ahn, Kwang; Litovich, Carlos; Kharfan-Dabaja, Mohamed A; Smith, Sonali M.; Sureda, Anna; Fenske, Timothy S.; Hamadani, Mehdi (Blood, 2018)
Introduction: AITL is a distinct clinicopathologic entity among the mature T-cell and NK-cell lymphomas, accounting for approximately 1-2% of all non-Hodgkin lymphomas. Although autologous HCT (auto-HCT) provides high response rates, there is a high relapse risk associated with this procedure. Allo-HCT may result in a lower risk of relapse in part due to a graft-versus-lymphoma effect mediated by alloreactive donor cells. The role of allo-HCT in AITL with advanced disease (prior auto-HCT failure, or chemorefractory state) is not well described. Using the CIBMTR registry, we report here the outcomes of AITL patients undergoing an allo-HCT. Methods: We evaluated 249 adult (≥18years) patients with AITL who received a first allo-HCT during 2000-2016. Patients receiving mismatched unrelated donor, cord blood or haploidentical donor transplantation were excluded due to small numbers. The primary end-point was overall survival (OS). Secondary endpoints included cumulative incidence of acute graft-versus-host disease (GVHD), chronic GVHD, non-relapse mortality (NRM), relapse/progression (R/P) and progression-free survival (PFS). Results: Baseline patient characteristics are summarized in Table. The median patient age was 56 years (range=21-77 years). The graft source was mainly peripheral blood. Median follow-up of survivors was 49 months (range=4-170 months). The cumulative incidence of grade 2-4 and grade 3-4 acute GVHD at day 180 were 36% (95% CI=30-42)% and 12 (95% CI=8-17)%, respectively. The cumulative incidence of chronic GVHD at 2 years was 58% (95% CI=51-64)%. The 1-year NRM was 19% (95% CI=14-24)%, while the 4-year R/P, PFS, and OS were 21% (95% CI=16-27)%, 49% (95% CI=42-56)% and 56% (95% CI=49-63)%, respectively [Figure]. On multivariate analysis, chemoresistant status at allo-HCT was associated with a significantly higher risk for progression (RR=1.73 95% CI=1.08-2.77), while KPS <90% was associated with a significantly higher risk of mortality (RR=3.46 95% CI=1.75 - 6.87). Subgroup analysis looking at the effect of prior auto-HCT (no prior auto-HCT vs prior auto-HCT), the 4-year PFS (50% vs 47%, p=0.60) and OS (57% vs 54%, p=0.70) were not significantly different. Similarly, on comparing the disease status at allo-HCT (CR1 vs CR>1 vs PR vs refractory), there was no significant difference in the 4-year PFS (58% vs 45% vs 47% vs 38%, p=0.41) or OS (70% vs 54% vs 50% vs 52%, p=0.27). The 1-year NRM was 24%, while the 4-year R/P, PFS, and OS in patients with refractory AITL were 32%, 38%, and 52%, respectively. The most common cause of death was organ failure. Conclusion: In this largest series of mostly advanced AITL patients, allo-HCT was shown to provide durable disease control (4-year PFS=47%) with a clear plateau in relapse at 1-year post-transplantation. Allo-HCT provided durable disease control even in patients with a failed prior auto-HCT and those subjects with refractory disease at the time of allografting. Kharfan-Dabaja:Alexion Pharmaceuticals: Speakers Bureau; Incyte Corp: Speakers Bureau; Seattle Genetics: Speakers Bureau. Smith:BMS: Consultancy; Portola: Honoraria. Sureda:Sanofi: Honoraria; Takeda: Consultancy, Honoraria, Speakers Bureau; Merck: Consultancy, Honoraria; Roche: Honoraria; BMS: Consultancy, Honoraria. Hamadani:Merck: Research Funding; Celgene Corporation: Consultancy; ADC Therapeutics: Research Funding; Sanofi Genzyme: Research Funding, Speakers Bureau; Ostuka: Research Funding; Janssen: Consultancy; MedImmune: Consultancy, Research Funding; Takeda: Research Funding; Cellerant: Consultancy.